The Role of Gut Microbiota Modification in Nonalcoholic Fatty Liver Disease Treatment Strategies - Hessam Yaghmaei; Amirhossein Bahanesteh; Masood Soltanipur; Sobhan Takaloo; Mahdi Rezaei; Seyed Davar Siadat (International Journal of Hepatology)
One of the most common chronic liver diseases is nonalcoholic fatty liver disease (NAFLD), which affects many people around the world. Gut microbiota (GM) dysbiosis seems to be an influential factor in the pathophysiology of NAFLD because changes in GM lead to fundamental changes in host metabolism. Therefore, the study of the effect of dysbiosis on the pathogenicity of NAFLD is important. European clinical guidelines state that the best advice for people with NAFLD is to lose weight and improve their lifestyle, but only 40% of people can achieve this goal. Accordingly, it is necessary to provide new treatment approaches for prevention and treatment. In addition to dietary interventions and lifestyle modifications, GM modification-based therapies are of interest. These therapies include probiotics, synbiotics, fecal microbiota transplantation (FMT), and next-generation probiotics. All of these treatments have had promising results in animal studies, and it can be imagined that acceptable results will be obtained in human studies as well. However, further investigations are required to generalize the outcomes of animal studies to humans.